2017
DOI: 10.1016/j.quascirev.2016.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetic chronology and paleoenvironmental records from drill cores from the Hetao Basin and their implications for the formation of the Hobq Desert and the Yellow River

Abstract: Reconstructing the Cenozoic environmental history of Hetao Basin, in the northern part of the Ordos Plateau in North China, is important not only for revealing the evolution of the Yellow River, but also for understanding the formation of the Hobq Desert. Here we present the stratigraphic framework of drill core DR01 with length of 2503.18 m, and the results of magnetostratigraphic and ESR dating and multi-proxy analyses of drill core WEDP05 with length of 274.60 m, from the Hetao Basin. The magnetostratigraph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 103 publications
(151 reference statements)
1
20
0
Order By: Relevance
“…mongolica . In addition, the divergence time of two geographic groups (Fig 4) is consistent with the formation of the Hobq Desert [56, 57], which, as a geographical barrier, may have blocked the genetic flow between the northern and southern groups. Previous studies have shown that the desert, as a geographical barrier, promotes the allopatric divergence of species [4].…”
Section: Discussionmentioning
confidence: 53%
“…mongolica . In addition, the divergence time of two geographic groups (Fig 4) is consistent with the formation of the Hobq Desert [56, 57], which, as a geographical barrier, may have blocked the genetic flow between the northern and southern groups. Previous studies have shown that the desert, as a geographical barrier, promotes the allopatric divergence of species [4].…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, the paleo-seismic studies revealed multiple ancient seismic events (Ran et al, 2003;. Drilling data in the Hetao Basin reveals that the maximum deposition thickness of the basin since the Quaternary is >2400 m, and the conversion of river-lacustrine deposition to aeolian deposition has occurred in multiple stages (Li et al, 2017). Previous authors based on thermochronology, regional stratigraphy, and structural geomorphology have shown that the mountains to the north of the Hetao Basin and the subsiding basins have experienced multiple periods of tectonic uplift, erosion and flattening.…”
Section: Tectonic Activitymentioning
confidence: 99%
“…In this study, we focused on the Hetao Rifted Basin to the north of the Ordos Block. As it acts as a paleolake during the last glacial-interglacial period (Li et al, 2007;Jia et al, 2016;Li et al, 2017;Cai et al, 2018), widely distributed lacustrine sediments of the Hetao paleolake could provide a sedimentary archive for recording the history of the evolution of the Hetao paleolake and its tectonics activity (Li et al, 2017;Cai et al, 2018;Yang et al, 2018, Yang et al, 2020. Based on a detailed investigation of the piedmont faults in the northern margin of the Hetao Basin, we documented a series of Late Quaternary angular unconformities within four sedimentary sections, including Hazigai, Haolaigou, Bianqianghao, and Huhesala.…”
Section: Introductionmentioning
confidence: 99%
“…Then, it started to flow out of the basin at the beginning of late Pleistocene. As a consequence, the paleolake started to shrink the size until it completely disappeared (Li et al 2017;Yang et al 2018).…”
Section: Study Areamentioning
confidence: 99%